Computational Fluid Dynamics (CFD) Modelling of Porous, Ultrafiltration Membranes - Staszak, Maciej; Staszak, Katarzyna (Journal of Membrane and Separation Technology, 2013)
This paper presents a finite element, three dimensional numerical model of flow in porous ceramic ultrafiltration membrane system together with experimental validation. The modelling is based on the computational fluid dynamics (CFD) technique. Major difficulty that arises during CFD modelling is appropriate and precise description of the porous media in terms of Navier-Stokes equation. Based on pressure-flow experimental measurements we present the approach for calculating the essential components of porous media flow resistance which are necessary for proper description of membrane process. The detailed description of a membrane was applied which accounts for support and membrane layer respectively. Moreover own procedure applied is presented, that is written using C language, for calculation of flow parameters. The model presented is in very good accordance with experimental results.